Sexual abuse and alcohol use among women in metropolitan São Paulo, Brazil: a general population study - Janaina Barbosa de Oliveira; Florence Kerr-Corrêa; Maria Cristina Pereira Lima; José Manoel Bertolote; Adriana Marcassa Tucci (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2013)
OBJECTIVE: The present study aimed at estimating the prevalence of lifetime sexual abuse among women and at investigating its association with alcohol consumption. METHOD: Population-based survey conducted through a representative and stratified cluster sample of metropolitan São Paulo. GENACIS questionnaire was used. Sample unit was the home, and all residents aged 18 years and over were interviewed. The outcome was lifetime sexual abuse. The univariate statistical analysis used the Rao-Scott test. Logistic regression was used for the multivariate analysis. RESULTS: The final sample totalized 1,216 women aged 18 years and over; the response rate was 75.0%. Most women were married (56.6%) and had less than 12 years of formal education (59.0%); 46.2% were aged between 25 and 44 years, and 44.4% had a low income. Of the respondents, 7.5% reported having suffered lifetime sexual abuse. Multiple logistic regression model showed an association between lifetime sexual abuse and being a heavy drinker (OR = 4.97) and being a former drinker (OR = 2.04). CONCLUSIONS: There are few population studies in Brazil investigating sexual abuse and its relation to alcohol use. Although the prevalence of lifetime sexual abuse in the present study was smaller than that observed in other studies, it is a highly expressive percentage on account of its social and economic impact, as well as its potential effect on the health system.